The Implementation of HOTS-Based English Learning in Junior High School During Online Classes - Widyastuti, Ni Wayan Suwardewi (Journal of Educational Study, 2023)
The purpose of this study is to learn the implementation of teaching and learning as well as the issue of the activities based on higher order thinking skills in English learning. This study was a descriptive qualitative study. The participants of this study were three English teachers in Junior High School 3 of Singaraja, Bali. The data were gathered using observation and direct interviews. The result of data analysis showed that the implementation of English learning during online classes had covered all the cognitive levels of Taxonomy Bloom, LOTS (lower order thinking skills), and HOTS (higher order thinking skills). However, the lack of training regarding HOTS-based learning caused teachers to have limited information about implementing the proper high-order thinking skills in the learning process. Thus, it has an impact on the problems that arise in implementing HOTS-based learning in online classes. This finding is intended to discover more about the implementation of junior high school English learning in HOTS-based online classes.